Experimental stress analysis - Dally, James W.; Riley, William F. (New York : McGraw-Hill, 1991)
This book is about: Elementary elasticity and fracture mechanics; Strain-measurement methods and related instrumentation; Optical methods of stress analysis; Coating methods; and Applications of statistics.
Keywords: Strains; Stresses; Photoelasticity; Strains and stresses; Photoelasticity; Strain gages